Resin composition, insulated wire and method for producing resin composition
The resin composition for insulated wires, featuring a combination of vinyl chloride resin, specific additives, and crosslinking aids, addresses the challenges of discoloration, gel fraction, and flame retardancy, achieving improved performance and environmental sustainability by being antimony-free and bisphenol A-free.
Patent Information
- Application Number
- JP2025029656
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-07-30
AI Technical Summary
Resin compositions used in insulated wires face challenges such as discoloration, inadequate improvement in gel fraction (crosslinking degree), and decreased flame retardancy when antimony and bisphenol A are not used, which hinders the advancement of antimony-free and non-bisphenol A-free resin compositions crosslinked with electron beams.
A resin composition comprising a vinyl chloride resin, a first additive group including titanium oxide and zinc stearate, and a second additive group including aluminum hydroxide, clay, and silica, with a gel fraction of 45% or more, and a crosslinking aid like trimethylolpropane triacrylate, which is crosslinked using electron beam irradiation with a specific product of crosslinking agent and irradiation intensity.
The solution effectively suppresses discoloration, enhances flame retardancy, and improves the gel fraction of the resin composition, while maintaining environmental performance by avoiding antimony and bisphenol A, thus improving the overall performance of insulated wires.
Smart Images

Figure 2025071344000004 
Figure 2025071344000001 
Figure 2025071344000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, an insulated wire, and a technique for producing the resin composition, and more particularly to an insulated wire conforming to the UL standard and a resin composition applicable to the insulated wire. [Background technology]
[0002] Insulated wires used in the internal wiring of electronic devices are required to be flame retardant to prevent the spread of flames along the insulated wire in the event of a fire caused by a malfunction or defect in the electronic device. For example, standards for the flame retardancy of insulated wires are set out in the US UL758 standard. The UL758 standard requires an optional vertical flame test (hereafter referred to as the "VW-1 test"). However, since most insulated wires have passed this "VW-1 test" and are certified as UL standards, the "VW-1 test" is almost a required item, even though it is an optional standard.
[0003] Polyvinyl chloride resin (PVC) is used as the main raw material for such insulated wire covering materials. Since polyvinyl chloride resin contains chlorine, a halogen element, in its chemical structure, polyvinyl chloride resin itself has high flame retardancy. However, since polyvinyl chloride resin is hard, it needs to be softened when used as a covering material for insulated wires. For this reason, a large amount of flammable plasticizer is added to the polyvinyl chloride resin. As a result, insulated wires using polyvinyl chloride resin cannot meet the above-mentioned flame retardancy standards unless a flame retardant is added.
[0004] Antimony trioxide has generally been used as a flame retardant. However, since antimony trioxide is a highly toxic substance, strict management is required during production, and it is a material that should be avoided. Furthermore, since antimony is a rare metal and its price is on the rise, it is also a material that should be avoided from the perspective of suppressing increases in the manufacturing costs of insulated electric wires.
[0005] For this reason, metal hydroxides such as aluminum hydroxide and magnesium hydroxide have come to be used as flame retardants to replace antimony trioxide.
[0006] For example, JP 2011-26427 A (Patent Document 1) describes a technology relating to a vinyl chloride resin composition containing a vinyl chloride resin, aluminum hydroxide and / or magnesium hydroxide, a plasticizer, and a non-lead stabilizer, in which the content of aluminum hydroxide and / or magnesium hydroxide is 8 parts by mass or more and 22 parts by mass or less per 100 parts by mass of the vinyl chloride resin, and the content of antimony is less than 1,000 ppm.
[0007] Furthermore, trimellitic acid esters are often used as plasticizers in vinyl chloride resin compositions. Some trimellitic acid esters contain bisphenol A as an antioxidant. In this regard, in recent years, from the viewpoint of environmental friendliness and environmental regulations, there has been a demand for so-called "non-bis" esters that do not use bisphenol A. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2011-26427 A Summary of the Invention [Problem to be solved by the invention]
[0009] Therefore, for example, resin compositions used for insulated wires are being made so-called "antimony-free" and "non-bisphenol A", that is, not containing antimony and bisphenol A. In this regard, the present inventors have newly found that, when resin compositions are made "antimony-free" and "non-bisphenol A", room for improvement as described below becomes apparent. (1) Discoloration of resin compositions caused by using flame retardants instead of antimony (2) The gel fraction (degree of cross-linking) does not improve (3) Deterioration of flame retardancy As a result of such a phenomenon, for example, progress in making resin compositions crosslinked with electron beams "antimony-free" and "non-bis-based" is currently hindered. Therefore, in order to progress in making resin compositions crosslinked with electron beams "antimony-free" and "non-bis-based," there is a need for a method for overcoming the above-mentioned room for improvement.
[0010] An object of the present invention is to provide a resin composition which is free of antimony and bisphenol A and thereby improves environmental performance, while suppressing discoloration and improving flame retardancy and gel fraction. [Means for solving the problem]
[0011] In one embodiment, the resin composition has a polyvinyl chloride resin, a first group of additives, a second group of additives, and a crosslinking aid, wherein the first group of additives includes titanium oxide and zinc stearate, and the second group of additives includes aluminum hydroxide, clay, and silica, and has a gel fraction of 45% by mass or more, a fraction value A obtained by dividing the total amount of the first group of additives to 100 parts by mass of the polyvinyl chloride resin by the total amount of the resin composition is 1% by mass or more and 2% by mass or less, a fraction value B obtained by dividing the total amount of the second group of additives to 100 parts by mass of the polyvinyl chloride resin by the total amount of the resin composition is 6.51% by mass or more and 15% by mass or less, and does not contain antimony or bisphenol A.
[0012] The insulated wire in one embodiment includes a conductor wire and an insulating layer covering the conductor wire, and the insulating layer is made of the above-mentioned resin composition.
[0013] In one embodiment, a method for producing a resin composition includes a step of crosslinking the above-mentioned resin composition by irradiating it with an electron beam, and the product of the amount of crosslinking aid added and the irradiation intensity of the electron beam irradiated during crosslinking is 9 or more. Effect of the Invention
[0014] According to one embodiment, it is possible to provide a resin composition that can suppress discoloration and improve flame retardancy and gel fraction while improving environmental performance by not containing antimony or bisphenol A. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a cross-sectional view showing a configuration example of an insulated wire. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] In all the drawings for explaining the embodiments, the same members are generally designated by the same reference numerals, and the repeated explanations thereof will be omitted. In addition, hatching may be applied even to plan views in order to make the drawings easier to understand.
[0017] <Summary of technical concept> As a result of extensive research, the present inventors have come up with a technical idea that can overcome the room for improvement described in the "Problems to be Solved by the Invention" section. Below, we will provide an overview of this technical idea.
[0018] The resin composition in this embodiment has a vinyl chloride resin, a first additive group, a second additive group, and a cross-linking aid. Here, the first additive group includes titanium oxide and zinc stearate. The second additive group includes aluminum hydroxide, clay, and silica. Furthermore, the cross-linking aid is trimethylolpropane triacrylate. Here, the gel fraction is 45% by mass or more. For example, the above-mentioned resin composition having a gel fraction of 45% by mass or more can be realized by the manufacturing method of the resin composition shown below.
[0019] That is, the method for producing a resin composition in this embodiment includes a step of crosslinking the above-mentioned resin composition by irradiating it with an electron beam, and the product of the amount of crosslinking aid added and the irradiation intensity of the electron beam irradiated during crosslinking is 9 or more.
[0020] According to the resin composition thus constituted, even if the resin composition is made "antimony-free" and "non-bis", it is possible to obtain a remarkable effect of overcoming the room for improvement that becomes apparent by making the resin composition "antimony-free" and "non-bis" {(1) the discoloration phenomenon of the resin composition caused by using a flame retardant replacing antimony, (2) the phenomenon that the gel fraction (degree of cross-linking) does not improve, and (3) the phenomenon that the flame retardancy decreases}. In other words, the technical idea of the present embodiment can be said to be an extremely excellent technical idea in that it can improve the performance of the resin composition by overcoming the room for improvement that becomes apparent by making the resin composition "antimony-free" and "non-bis" while providing a resin composition with a small environmental load by making the resin composition "antimony-free" and "non-bis".
[0021] In particular, the present inventors conducted further detailed studies based on the above-mentioned technical idea and discovered a new resin composition configuration that is desirable for achieving the above-mentioned remarkable effects. Therefore, a new example of the resin composition configuration will be described below.
[0022] <Configuration of Resin Composition> An example of the composition of a resin composition embodying the above-mentioned technical concept will now be described.
[0023] The resin composition in the present embodiment has the following composition.
[0024] <<Vinyl chloride resin>> The resin composition contains a vinyl chloride resin (PVC) as a main component. Here, the vinyl chloride resin in the present embodiment is preferably composed of one or more vinyl chloride resins having a "K value" of, for example, 75.7 or more and 85.6 or less, or composed of two or more vinyl chloride resins having a "K value" of 71.6 or more and 85.6 or less. This is because, according to findings obtained as a result of intensive studies by the present inventors, it is difficult to improve the long-term heat resistance after electron beam irradiation with a single vinyl chloride resin having a "K value" of 71.6, whereas it has been found that the long-term heat resistance after electron beam irradiation can be improved by combining it with a vinyl chloride resin having a "K value" of 84 or more and 85.6 or less.
[0025] In the present embodiment, as the one or more types of vinyl chloride resins having a "K value" of 75.7 to 85.6, vinyl chloride resins having a "K value" in the range of 75.7 to 78.1, commonly known as a "degree of polymerization P=1700", are used. Here, the "K value" is not the degree of polymerization itself, but is an index that is proportional to the degree of polymerization.
[0026] From the viewpoint of improving other physical properties of the resin composition, such as flexibility and cold resistance, a "copolymer" in which vinyl acetate or ethylene is copolymerized with vinyl chloride resin may be used.
[0027] <<Plasticizer>> The resin composition includes, for example, a plasticizer containing an antioxidant.
[0028] Although not particularly limited, it is desirable to use a trimellitate-based plasticizer represented by a trimellitic acid ester as the plasticizer, and examples thereof include tri-2-ethylhexyl trimellitate, tri-normal alkyl trimellitate, triisononyl trimellitate, and isodecyl trimellitate.
[0029] In this embodiment, the antioxidant is, for example, a phenol-based antioxidant, which is composed of a substance having a structure with three or more hydroxyl groups in one molecule, and the amount of the phenol-based antioxidant added is 0.5 mass% or less of the total amount of the plasticizer added. According to the study by the present inventors, it has been newly found that such a plasticizer configuration is desirable from the viewpoint of overcoming the above-mentioned room for improvement. Furthermore, according to further study by the present inventors, it has been found that a configuration in which 20 mass% or less of the total amount of trimellitic acid ester added is replaced with chlorinated polyethylene is also desirable from the viewpoint of overcoming the above-mentioned room for improvement.
[0030] In this regard, the effectiveness of the plasticizer in the present embodiment is verified in the examples described later. Specifically, in the examples, tri-normal alkyl trimellitate (N08A: n-TOTM manufactured by Kao Corporation) or triisononyl trimellitate (UN302: manufactured by Taiwan UPC Co., Ltd.) is evaluated. Here, tri-normal alkyl trimellitate (N08A: n-TOTM manufactured by Kao Corporation) is a plasticizer to which 0.3% by mass of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane is added. On the other hand, triisononyl trimellitate (UN302: manufactured by Taiwan UPC Co., Ltd.) is a plasticizer to which 0.35% by mass of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane is added.
[0031] In addition, as a comparative plasticizer for evaluating the effectiveness of the plasticizer (containing antioxidant) used in this embodiment, a plasticizer (Irga 1010 0.5 mass% added product) in which triisononyl trimellitate without antioxidant is heated to 60°C and 0.5 mass% of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane is dissolved is also evaluated. Furthermore, as a comparative plasticizer, tri-normal alkyl trimellitate (N08:n-TOTM manufactured by Kao Corporation) is also evaluated. This tri-normal alkyl trimellitate (N08:n-TOTM manufactured by Kao Corporation) is a plasticizer to which bisphenol A is added.
[0032] <<Stabilizer>> The resin composition contains, for example, a stabilizer, such as hydrotalcite, stearic acid, stearate metal soap, stearoylbenzoylmethane, dibenzoylmethane, dibenzoylmethane salt, rutile-type titanium oxide, trihydroxyethyl isocyanate, a phenol-based antioxidant, silica, calcium hydroxide, polyethylene oxide, talc, or benzotriazole.
[0033] Here, the amount of hydrotalcite contained in the stabilizer is desirably 5 parts by mass or more and less than 15 parts by mass with respect to 100 parts by mass of vinyl chloride resin. This is because, when the amount of hydrotalcite added is less than 5 parts by mass, heat resistance performance is not exhibited, while when the amount of hydrotalcite added is 15 parts by mass or more, molding processability during kneading and extrusion molding of the resin composition is deteriorated. Furthermore, it is desirably that the fraction value A obtained by dividing the total amount of zinc stearate and titanium oxide added by the total amount of the resin composition with respect to 100 parts by mass of vinyl chloride resin is 1% by mass or more and 2% by mass or less. This is because, when the fraction value A is less than 1% by mass, the effect of suppressing discoloration during electron beam irradiation is insufficient, while when the fraction value is greater than 2% by mass, molding processability during kneading and extrusion molding of the resin composition is deteriorated and material costs are increased.
[0034] <<Titanium oxide>> The titanium oxide in this embodiment is used as a masking agent. Examples of this titanium oxide include titanium oxide produced by the "sulfuric acid method" in which titanium oxide hydrate obtained by hydrolysis of titanium sulfate solution is calcined, and the "chlorine method" in which titanium halide is oxidized in gas phase. Here, for example, the average particle size of the primary particles measured by electron microscopy is about 0.1 μm or more and 1.0 μm or less, and the crystal form can be anatase type or rutile type.
[0035] The titanium oxide used in this embodiment is a two-layer coated rutile titanium oxide produced by the "chlorine method", and the selected grade is, for example, "R103" from Chemours. That is, the titanium oxide used in this embodiment is covered with a first coating layer that covers the titanium oxide and a second coating layer that covers the first coating layer. Here, for example, the first coating layer is made of aluminum oxide, while the second coating layer is made of polyol. In this case, the polyol contains any one of trimethylolmethane, trimethylolethane, trimethylolpropane, and pentaerythritol.
[0036] Here, the technical significance of using titanium oxide coated with the first coating layer and the second coating layer will be explained. For example, the first coating layer works to activate polymers and plasticizers by titanium oxide and to suppress quinone color development in the presence of phenolic antioxidants, while the second coating layer exerts the function of further suppressing these and also works to improve dispersibility in resin compositions. In other words, the first coating layer has the function of suppressing quinone color development, and the second coating layer has the function of further suppressing quinone color development and improving dispersibility in resin compositions.
[0037] There is no problem in applying titanium oxide (R820) that is manufactured by the "sulfuric acid method" and is composed only of a first coating layer (e.g., a composite of aluminum, silica, and zinc), but the discoloration suppression effect described above is not obtained. "R820" is titanium oxide with an average particle size of 0.26 μm and a titanium content of 93 mass %. In contrast, when titanium oxide manufactured by the "chlorine method" and coated with a first coating layer and a second coating layer is used, a remarkable discoloration suppression effect is obtained as described above. This point is the technical significance of using titanium oxide coated with a first coating layer and a second coating layer, and is a new finding made by the present inventor.
[0038] The titanium oxide concentration in the two-layer coated rutile titanium oxide, such as "R103," is preferably 90% by mass or more, and more preferably 95% by mass or more, from the viewpoint of suppressing discoloration caused by impurities due to electron beam irradiation. The coating amount of aluminum oxide constituting the first coating layer is preferably 1.7% by mass or more and 4.3% by mass or less, and the coating amount of polyol constituting the second coating layer is preferably 0.15% by mass or more and 0.3% by mass or less.
[0039] The average particle size of the double-layer coated rutile-type titanium oxide is preferably 0.2 μm or more and 0.35 μm or less.
[0040] The above-mentioned "R103" is titanium oxide having a purity of 96% by mass, a coating amount of aluminum oxide of 3.2% by mass, a coating amount of polyol of 0.2% by mass, and an average particle size of 0.23 μm.
[0041] <<Filling agent>> The resin composition includes, for example, a filler. The filler may be composed of clay (silicate). In particular, the clay is preferably a sintered calcined clay.
[0042] <<Flame retardants>> The resin composition contains a flame retardant. The flame retardant has aluminum hydroxide and silica. Here, the fraction value B obtained by dividing the total amount of aluminum hydroxide, clay, and silica added by the total amount of the resin composition with respect to 100 parts by mass of vinyl chloride resin is preferably 6% by mass or more and 15% by mass or less. This is because, if the fraction value B is less than 6% by mass, it becomes difficult to exhibit flame retardancy, whereas if the fraction value B is greater than 15% by mass, it becomes difficult to suppress discoloration due to electron beam irradiation.
[0043] <<Crosslinking agent>> The resin composition is crosslinked in order to improve the properties. In this case, the resin composition contains, for example, a crosslinking aid. An example of the crosslinking aid is trimethylolpropane triacrylate.
[0044] Here, by increasing the amount of trimethylolpropane triacrylate added, the gel fraction (degree of cross-linking) can be improved. On the other hand, the gel fraction can also be improved by increasing the irradiation intensity of the electron beam. However, if the irradiation intensity of the electron beam is high, discoloration due to the irradiation of the electron beam is likely to occur. For this reason, from the viewpoint of suppressing coloration, it is necessary to avoid increasing the irradiation intensity of the electron beam too much. In other words, it is desirable to obtain a high gel fraction even if the irradiation intensity of the electron beam is low. Therefore, in this embodiment, in order to obtain a high gel fraction even if the irradiation intensity of the electron beam is low, the product of the amount of trimethylolpropane triacrylate added to 100 parts by mass of vinyl chloride resin and the irradiation intensity of the electron beam is applied as an evaluation index for the gel fraction. At this time, from the viewpoint of obtaining a high gel fraction (gel fraction of 45% by mass or more), it is desirable to adjust the amount of trimethylolpropane triacrylate added and the irradiation intensity of the electron beam so that the product of the amount of cross-linking assistant added and the irradiation intensity is 9 or more.
[0045] <<Other additives>> The resin composition may contain other additives as necessary. Specifically, the resin composition may contain ultraviolet absorbers, light stabilizers, lubricants, colorants, processability improvers, and other modifiers, either alone or in combination of two or more.
[0046] The resin composition according to the present embodiment is configured as described above. In the following, an example of the configuration of an insulated wire using this resin composition will be described.
[0047] <Insulated wire structure> FIG. 1 is a cross-sectional view showing an example of the configuration of an insulated wire.
[0048] As shown in Fig. 1, the insulated wire 10 has a conductor wire 1 and an insulating layer 2 that covers the outer periphery of the conductor wire 1. In this case, for example, the resin composition in the present embodiment described above is used for the insulating layer 2. As shown in Fig. 1, the insulating layer 2 may be configured to directly cover the conductor wire 1, or may be used as a sheath material that covers the insulated wire 10.
[0049] The insulated electric wire 10 in this embodiment can be manufactured by coating the conductor 1 with a resin composition by a molding means such as extrusion coating, and then crosslinking the resin composition that constitutes the insulating layer 2 by a method such as electron beam irradiation.
[0050] The extrusion coating is carried out by kneading the resin composition before crosslinking using a roll, Banbury machine, extruder, or the like to obtain a pellet compound, and then extruding the resin composition into a conductive wire 1 using an extruder for electric wires equipped with a crosshead die so as to cover the conductive wire.
[0051] The conductor wire 1 to be covered may have an outer diameter of, for example, 0.15 mm or more and about 7 mm. The conductor wire 1 may be, but is not limited to, a conductor wire made by twisting tin-plated soft copper wires.
[0052] The outer diameter of the insulated wire 10 is, for example, about 0.4 mmφ to 11 mmφ, and its applications include wiring in high-temperature parts of devices such as dryers, rice cookers, transformer outlets, lighting fixtures, and air conditioners.
[0053] In the insulated electric wire 10 thus configured, the resin composition in the present embodiment described above is used as the resin composition constituting the insulating layer 2. As a result, the insulated electric wire 10 can overcome the room for improvement that becomes apparent due to the "antimony-free" and "non-screw" resin composition while realizing the "antimony-free" and "non-screw" resin composition. That is, in the present embodiment, it is possible to provide an insulated electric wire 10 with a small environmental load while improving the performance of the insulated electric wire 10. In other words, the insulated electric wire 10 in the present embodiment can achieve both environmental performance and electric wire performance.
[0054] In the following, experimental results are described which support the idea that an insulated electric wire embodying the technical concept of the present embodiment can improve the wire performance of the insulated electric wire itself while improving the environmental friendliness by being "antimony-free" and "screw-free." However, the technical concept of the present embodiment is not limited to the examples shown below.
[0055] <Example> <<Preparation of resin composition>> The materials were mixed in the ratios shown in Table 1 below, and then kneaded and mixed in an oven roll mixer heated to 170°C and pelletized to produce the resin compositions of Examples 1 to 10, Comparative Examples 1 and 2, and Reference Example 1. The resin compositions of Examples 1 to 10 and Comparative Examples 1 and 2 do not contain antimony or bisphenol A, and are "antimony-free" and "non-bisphenol". On the other hand, the resin composition of Reference Example 1 is a resin composition containing antimony and bisphenol A, and is not "antimony-free" or "non-bisphenol".
[0056] [Table 1]
[0057] <<Making insulated wires>> A conductor wire (outer diameter: 0.76 mmφ) made by twisting together 17 tin-plated soft copper wires with an outer diameter of 0.16 mmφ was used as the conductor wire. A resin composition was formed on this conductor wire by melt extrusion, and then an insulated electric wire (sample) was produced by covering the conductor wire with the resin composition. Specifically, a plurality of samples were produced by covering the conductor wire with the resin composition in each of Examples 1 to 10, Comparative Examples 1 to 2, and Reference Example 1. The thickness of the insulating layer made of the resin composition was 0.5 mm. The electric wire manufacturing conditions were a cylinder temperature of 170°C, a head temperature of 180°C, and a linear speed of 20 m / min. Thereafter, an electron beam irradiation machine was used to irradiate the insulated electric wire with an electron beam at a specified irradiation intensity, thereby causing a crosslinking reaction in the resin composition, and the final insulated electric wire was produced.
[0058] <<Evaluation of insulated wires>> The prepared insulated wires were evaluated for the following items.
[0059] (1) Discoloration after electron beam irradiation When the materials were mixed and kneaded in the ratios shown in Table 1, insulated wires were prepared by coloring them with the materials shown in Table 2, and then cut into 10 cm lengths to evaluate discoloration before and after electron beam irradiation. Here, those that showed no visual difference in hue before and after electron beam irradiation were marked with "◯", and those that showed a difference in hue were marked with "X".
[0060] [Table 2]
[0061] (2) Flame retardancy The insulated wires of Examples 1 to 10, Comparative Examples 1 and 2, and Reference Example 1 were subjected to a "VW-1 test" in accordance with UL758, with those that passed being marked with "O" and those that failed being marked with "X".
[0062] (3) Gel fraction The insulating layer of the prepared insulated wire was peeled off and cut into pieces of 1 mm square or less, and then the gel was extracted under tetrahydrofuran at 70° C. for 20 hours. The extracted gel was then dried to calculate the gel fraction.
[0063] Those with a gel fraction of 45% by mass or more were rated as "Good," and those with a gel fraction of less than 45% by mass were rated as "Poor." If the gel fraction is less than 45% by mass, there is a possibility that the practical characteristic of the electric wire, "300°C 3-second solder resistance," may not be obtained.
[0064] (4) Evaluation results The evaluation results for the above-mentioned evaluation items are shown in Table 3.
[0065] [Table 3]
[0066] As shown in Table 3, in Examples 1 to 10 in which the technical idea of the present embodiment is embodied, good results were obtained in all evaluation items. On the other hand, in Comparative Examples 1 and 2 in which the technical idea of the present embodiment is not applied, it was not possible to achieve all three evaluation items. That is, Comparative Example 1 failed all three evaluation items. Moreover, Comparative Example 2 failed the gel fraction. Note that, in Reference Example 1 in which a resin composition containing antimony and bisphenol A was used, good results were obtained in all evaluation items, but "antimony-free" and "non-bisphenol A" were not achieved.
[0067] The above evaluation results support that the insulated electric wires (Examples 1 to 10) in which the technical idea of this embodiment is embodied can improve the performance of the insulated electric wire, such as suppression of discoloration, improved flame retardancy, and improved gel fraction, while realizing environmentally friendly "antimony-free" and "non-screw" properties. Therefore, it can be seen that the technical idea of this embodiment is extremely excellent in terms of improving the performance of the insulated electric wire.
[0068] The invention made by the inventor has been specifically described above based on the embodiment thereof. However, it goes without saying that the present invention is not limited to the above embodiment, and various modifications can be made without departing from the spirit of the invention. [Explanation of symbols]
[0069] 1 conductor 2. Insulation layer 10 Insulated wire
Claims
1. A resin composition comprising a vinyl chloride resin, a first additive group, a second additive group, and a crosslinking aid, The first additive group includes titanium oxide and zinc stearate, The second group of additives includes aluminum hydroxide, clay, and silica; The gel fraction is 45% by mass or more, A fraction A obtained by dividing the total amount of the first additive group relative to 100 parts by mass of the vinyl chloride resin by the total amount of the resin composition is 1% by mass or more and 2% by mass or less, A fraction value B obtained by dividing the total amount of the second additive group relative to 100 parts by mass of the vinyl chloride resin by the total amount of the resin composition is 6.51% by mass or more and 15% by mass or less, A resin composition that is free of antimony and bisphenol A.
2. The resin composition according to claim 1, The first additive group is Stearoyl benzoylmethane, Trihydroxyethyl isocyanate, A resin composition comprising:
3. The resin composition according to claim 1 or 2, The resin composition includes hydrotalcite.
4. The resin composition according to claim 3, The resin composition contains the hydrotalcite in an amount of 5 parts by mass or more and less than 15 parts by mass per 100 parts by mass of the vinyl chloride resin.
5. The resin composition according to any one of claims 1 to 4, The titanium oxide is A first coating layer covering the titanium oxide; A second coating layer covering the first coating layer; The resin composition is covered with
6. The resin composition according to claim 5, The first coating layer is made of aluminum oxide, The second coating layer is a resin composition composed of a polyol.
7. The resin composition according to claim 6, The resin composition, wherein the polyol contains any one of trimethylolmethane, trimethylolethane, trimethylolpropane, and pentaerythritol.
8. The resin composition according to any one of claims 1 to 7, The resin composition has a plasticizer containing an antioxidant, The antioxidant is composed of a substance having a structure having three or more hydroxyl groups in one molecule, The resin composition, wherein the amount of the antioxidant added is 0.5 mass % or less of the total amount of the plasticizer added.
9. The resin composition according to claim 8, The plasticizer comprises a trimellitic acid ester, The resin composition, wherein the antioxidant is a phenol-based antioxidant.
10. The resin composition according to claim 8, The plasticizer is Trimellitic acid ester, Chlorinated polyethylene; A resin composition comprising:
11. A conducting wire, an insulating layer covering the conductor; An insulated wire comprising: The insulated wire, wherein the insulating layer is made of the resin composition according to any one of claims 1 to 10.
12. The composition includes a vinyl chloride resin, a first additive group, a second additive group, and a cross-linking aid, The first additive group includes titanium oxide and zinc stearate, The second group of additives includes aluminum hydroxide, clay, and silica; A fraction A obtained by dividing the total amount of the first additive group relative to 100 parts by mass of the vinyl chloride resin by the total amount of the resin composition is 1% by mass or more and 2% by mass or less, A fraction value B obtained by dividing the total amount of the second additive group relative to 100 parts by mass of the vinyl chloride resin by the total amount of the resin composition is 6.51% by mass or more and 15% by mass or less, A method for producing a resin composition that is free of antimony and bisphenol A and has a gel fraction of 45 mass% or more, comprising the steps of: The method includes a step of crosslinking the resin composition by irradiating the resin composition with an electron beam, A method for producing a resin composition, wherein the product of the amount of the crosslinking auxiliary added and the irradiation intensity of the electron beam is 9 or more.
Citation Information
Patent Citations
Flame-retardant, vinyl chloride-based resin molded product
JP2001192520A
Polyvinyl chloride resin composition, insulated wire, cable and those manufacturing method
JP2004285275A
Vinyl chloride resin composition, insulated wire, cable, method for producing insulated wire, and method for producing cable
JP2020186286A
Vinyl chloride resin composition and insulated wire using the same
JP2011026427A